Mode of Action of the Toxin from Pseudomonas phaseolicola: I. Toxin Specificity, Chlorosis, and Ornithine Accumulation - Patil, Suresh S. (1972)
The specificity of the Pseudomonas phaseolicola toxin for enzyme inhibition and its relationship to toxin-induced chlorosis in bean leaves (Phaseolus vulgaris L.) was examined. The toxin showed no significant inhibitory activity against glutamine synthetase, glutamine transferase, carbamyl phosphate synthetase, aspartate carbamoyltransferase, or arginase at concentrations 100-fold higher than that needed to inhibit ornithine carbamoyltransferase by 50%. Protection from and reversal of toxin-induced chlorosis in bean leaves was attempted with several amino acids. Aside from protection with l-citrulline which was previously reported, only l-arginine-HCl and to a minor extent l-leucine and l-glutamine showed protection from chlorosis. l-Citrulline and l-arginine-HCl (but not l-glutamine and l-leucine) also reversed toxin-induced chlorosis. Ultrastructurally, cells from toxin-treated chlorotic tissues showed no observable changes as compared to nontreated tissues. This, together with the ability of the two amino acids to reverse chlorosis, indicated that the toxin causes a reversible biochemical lesion in treated tissue. While tissues from bean plants inoculated with P. phaseolicola showed a large accumulation of ornithine, toxin-treated tissues showed no accumulation of ornithine. The latter finding indicated that in addition to the ornithine carbamoyltransferase inhibitor, the pathogen may produce inhibitors of other ornithine metabolizing enzymes in inoculated tissues.